ANALYSIS OF ALTERATIONS IN FECAL METAGENOMIC PROFILE IN AUTISM SPECTRUM DISORDER - Sobia Khurshid; Syeda Marriam Bakhtiar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
An ample repository of data suggests the connections between gut microbiota and Autism Spectrum Disorder (ASD), however, no consistent results are yet obtained as which gut bacterial genera are in lower and higher abundance in autistic and control group. Moreover, there is a lack of research concerning this issue in Pakistani population. The present study has been designed to assess the variations in gut microbial composition in autistic and control/neurotypically growing children group. For that matter, 2 autistic children and 2 normal children were enrolled in the study. Various social. demographic, and diet-related queries were taken through questionnaires. 16S rRNA sequencing was employed to assess the fecal samples to delineate the alterations in fecal metagenomic profile in autistic and normal group. Less diversity and richness was observed in ASD group as compared to the control group in calculating alpha diversity. Beta diversity exhibited differential clustering in both groups. Significant microbial differences were observed at phylum and genus level. At phylum level, the relative abundance of Proteobacteria and at the genus level, Lachnospiraceae UCG-004 was found to be lower in ASD group as compared to the control group. This research highlights the variations in gut microbial composition in autistic children and neurotypically growing ones in Pakistan.